Neutrophil phenotypes in health and disease - Hellebrekers, Pien (Eur J Clin Invest, 2018)
Neutrophils are one of the most important effector cells of the innate immune response (1). They are traditionally seen as a homogenous population of short‐lived cells mainly involved in the defence against extracellular microorganisms by phagocytosis and intracellular killing (1,2). The cells contain a large armamentarium that aids in this function and ranges from the production of reactive oxygen species by a membrane‐bound NADPH oxidase to cytotoxic proteins and peptides residing in the different granules present in the cytoplasm (3). Recently, the view of neutrophils belonging to a homogenous population of cells has been challenged, and several neutrophil phenotypes have been described that exhibit specialized functions, such as involvement in tissue repair, tumour killing and immune regulation (4). It is not clear whether these cells belong to separate parallel lineages originating from the bone marrow or that neutrophils become instructed in the distant tissues, thus changing their phenotypes. In addition, functional heterogeneity in a phenotypically homogenous population of neutrophils adds to the complexity of neutrophil phenotypes(5). This article will review the current literature describing the heterogeneity within the neutrophil compartment with respect to both phenotype and function in health and disease.